2015
DOI: 10.3345/kjp.2015.58.11.427
|View full text |Cite
|
Sign up to set email alerts
|

Severe vitamin D deficiency in preterm infants: maternal and neonatal clinical features

Abstract: PurposeWe investigated the vitamin D status of preterm infants to determine the incidence of vitamin D deficiency.MethodsA total of 278 preterm infants delivered at Kyungpook National University Hospital between January 2013 and May 2015 were enrolled. The serum concentrations of calcium, phosphorous, alkaline phosphatase, and 25-hydroxyvitamin D (25-OHD) were measured at birth. We collected maternal and neonatal data such as maternal gestational diabetes, premature rupture of membranes, maternal preeclampsia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
4
30
1
1
Order By: Relevance
“…Burris et al (18) did not see any linear correlation between vitamin D level and gestational week. Park et al (20) reported insignificant correlation of vitamin D levels with gestational age and birth weight.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Burris et al (18) did not see any linear correlation between vitamin D level and gestational week. Park et al (20) reported insignificant correlation of vitamin D levels with gestational age and birth weight.…”
Section: Resultsmentioning
confidence: 98%
“…Park et al (20) found vitamin D level as 10.7±6.4 ng/mL in a study of 278 cases with a mean gestational age of 33±2 weeks. In the cohort of Park et al (20) 91% of newborn babies have vitamin D deficiency and there is severe vitamin D deficiency in 51%. In our study the mean vitamin D level was higher and vitamin D deficiency rates were lower when compared to the above studies (19,20).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…1,2 The results from previous studies indicated that the vitamin D levels in Korean preterm infants were lower than those in infants in Northern European countries. 3,4 Vitamin D deficiency remains a common micronutrient disorder despite of encouragement to vitamin D supplements. Vitamin D plays an important role in calcium and bone metabolism, and potential associations between vitamin D and immune modulators, erythropoiesis, and iron homeostasis have been reported.…”
Section: Introductionmentioning
confidence: 99%